2012
DOI: 10.2176/nmc.52.835
|View full text |Cite
|
Sign up to set email alerts
|

Visual Disturbance Following Shunt Malfunction in a Patient With Congenital Hydrocephalus

Abstract: A 25-year-old woman presented with complaints of nausea and headache. She had been treated with a ventriculoperitoneal shunt for hydrocephalus when she was 7 months old. Her bilateral optic discs showed moderate atrophy. Right visual acuity allowed only perception of hand movement and left visual acuity was 0.02 (1.2). Computed tomography (CT) showed mild ventricular dilation but no periventricular lucency. Intracranial pressure (ICP) was not high when the shunt valve was punctured. Her visual acuity deteriora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 14 publications
1
17
0
5
Order By: Relevance
“…[ 6 ] Decreased visual acuity has rarely been documented in the literature but is considered an atypical presentation along with other presentations such as seizures, abdominal pseudocyst, syringomyelia, cranial nerve palsies, and hemiparesis. [ 3 4 6 7 ] Although rare, decreased visual acuity could be a portent of permanent visual impairment such has been reported in 1.8% of all children experiencing an episode of raised intracranial pressure due to shunt malfunction. [ 7 ] It has also been reported that in such cases the patient need not have features of raised intracranial pressure or papilledema.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 6 ] Decreased visual acuity has rarely been documented in the literature but is considered an atypical presentation along with other presentations such as seizures, abdominal pseudocyst, syringomyelia, cranial nerve palsies, and hemiparesis. [ 3 4 6 7 ] Although rare, decreased visual acuity could be a portent of permanent visual impairment such has been reported in 1.8% of all children experiencing an episode of raised intracranial pressure due to shunt malfunction. [ 7 ] It has also been reported that in such cases the patient need not have features of raised intracranial pressure or papilledema.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 4 6 7 ] Although rare, decreased visual acuity could be a portent of permanent visual impairment such has been reported in 1.8% of all children experiencing an episode of raised intracranial pressure due to shunt malfunction. [ 7 ] It has also been reported that in such cases the patient need not have features of raised intracranial pressure or papilledema. [ 2 3 4 7 ] Cerebral infarcts in the posterior cerebral artery territory have been documented.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations